The Applicability of the Promotion of Access to Information Act 2 of 2000 and Promotion of Administrative Justice Act 3 of 2000 to the South African Legal Practice Council - Hona, Zakuthwani Alfred (Department of Public Law, 2020)
Section 33 of the Constitution guarantees to everyone the right to just administrative action that is lawful, reasonable and procedurally fair. The Promotion of Administrative Justice Act 3 of 2000 (“PAJA”) was promulgated to give effect to give effect to this fundamental right as envisaged in s 33(3) of the Constitution. Section 32 of the Constitution also guarantees to everyone the right of access to information. The Promotion of Access to Information Act 2 of 2000 (“PAIA”) was promulgated to give effect to this fundamental right as contemplated in s 32(2) of the Constitution. This thesis considers the extent to which the provisions of PAJA may be applicable to the actions of the South African Legal Practice Council (“the LPC”). It also considers the extent to which the provisions of PAIA may be applicable to the records of the LPC. Some remedial legislative amendments to the provisions of both PAJA and PAIA are recommended with the view of addressing certain identified legal obstacles. The proposed legislative amendments will enhance the exercise, realisation, enforcement and protection of both the right to just administrative action and the right of access to information.